Mehdi Golshani's Thoughts on Science in Islam - Wiwik Prasetiyo Ningsih; Mohammad Zainal Hamdy; 2Vicky Izza El Rahma; Atifatul Unsi; Moh. Mofid (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
Islam and Science cannot be separated, especially in modern life. The signs in the Qur'an, which is the holy book of Islam, have been real and proven not to contradict science. In fact, the Qur'an is an early clue to the absurdity that occurs in the universe. Islam and Science have been proven to be able to play a real role in developing human life together. Mehdi Golshani is one of the Islamic thinkers who studies religion and science. Where the purpose of this paper is to present his thoughts on science, especially in the view of Islam. This paper uses qualitative methods included in library research by collecting data and information from credible books and journals which results in Mehdi Golshani's thinking can be used as a way to solve all in the universe that occur not by accident but are controlled directly by God.